2016 10th European Conference on Antennas and Propagation (EuCAP) 2016
DOI: 10.1109/eucap.2016.7481501
|View full text |Cite
|
Sign up to set email alerts
|

LTE MIMO antenna using unbroken metallic rim and non resonant CCE element

Abstract: This paper presents a new two-element multiple input multiple output (MIMO) antenna for LTE application using an unbroken metallic rim as the primary antenna and a non-resonant capacitive coupling element (CCE) as a diversity antenna. The primary antenna covers 698-960 MHz and 1710-2690 MHz and the diversity antenna cover 1710-2690 MHz Average efficiencies above 70% and 50% have been achieved by the metallic rim antenna and non-resonant CCE respectively. A trapezoidal shaped feed is used to improve the high ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Problems caused by the increased amount of metal have been countered by new type of antennas that are integrated into the housing structure [1][2][3][4][5][6][7]. Previous studies have shown promising performance with different antenna configurations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Problems caused by the increased amount of metal have been countered by new type of antennas that are integrated into the housing structure [1][2][3][4][5][6][7]. Previous studies have shown promising performance with different antenna configurations.…”
Section: Introductionmentioning
confidence: 99%
“…The first solutions include only metallic side frame. Grounding the frame from few locations creates a dual-loop antenna [1,2], which excites several resonant modes. Loop antennas generally have been a popular choice as presented in [3][4][5]9].…”
Section: Introductionmentioning
confidence: 99%